Legal Aspects of Defence Procurement in the European Union: Funding Incentives and Regulatory Shields - Kovács, Bálint (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
This chapter presents an analysis of regulations established at the European Union level, particularly aimed at improving common defence capabilities by encouraging industrial development. It critically examines the specific instruments utilised by States in the course of defence procurement. First, it focuses on the “Defence Package”, outlining the purpose and content of this regulatory attempt to harmonise Member States’ legislation on the procurement and transfer of defence-related products. It then analyses the potential reasons for its limited application. This is followed by an inquiry into the potential for funding schemes to act as incentives to boost cooperative defence spending and encourage Member States to engage in the harmonised development of the European defence industry. The analysis also briefly evaluates the situation of small and medium-sized enterprises, particularly those within the novel funding schemes. Finally, it addresses the specific instruments regularly used by States in defence procurement, with an emphasis on defence offsets as a means for defence industrial protectionism.Keywords: defence package, procurement, transfers, funding, SMEs, offsets